Carryover of Common Corn and Soybean Herbicides to Various Cover Crop Species. (6th February 2017) - Cornelius, Cody D.; Bradley, Kevin W.
Abstract : The recent interest in cover crops as component of Midwest corn and soybean production systems has led to the need for additional research, including the effects of residual corn and soybean herbicide treatments on fall cover crop establishment. Field studies were conducted in 2013, 2014, and 2015 in Columbia, Missouri to investigate the effects of common residual herbicides applied in corn and soybean on establishment of winter wheat, tillage radish, cereal rye, crimson clover, winter oat, Austrian winter pea, Italian ryegrass, and hairy vetch. Cover crops were evaluated for stand and biomass reduction 28 d after emergence (DAE). Rainfall from herbicide application to cover crop seeding date was much greater in 2014 and 2015, which resulted in less carryover in these years compared to 2013. When averaged across all herbicides evaluated in these experiments, the general order of sensitivity of cover crops to herbicide carryover, from greatest to least was Austrian winter pea=crimson clover>oilseed radish>Italian ryegrass>hairy vetch>wheat >winter oat>cereal rye. Cereal rye had the fewest instances of biomass or stand reduction with only four out of the 27 herbicides adversely effecting establishment. Pyroxasulfone consistently reduced Italian ryegrass and winter oat biomass at least 67% in both the corn and soybean experiments. In the soybean experiment, imazethapyr- and fomesafen-containing products resulted in severe stand and biomass reduction in both years while flumetsulam-containing products resulted in the greatest carryover symptoms in the corn experiment. Results from these experiments suggest that several commonly used corn and soybean herbicides have the potential to hinder cover crop establishment, but the severity of damage will depend on weather, cover crop species, and the specific herbicide combination. Abstract : El reciente interés en el uso de cultivos de cobertura como componente de los sistemas de producción de maíz y soja en el medio oeste ha llevado a la necesidad de realizar investigación adicional que incluya los efectos de los tratamientos de herbicidas residuales en maíz y soja sobre el establecimiento de cultivos de cobertura en el otoño. Estudios de campo fueron realizados en 2013, 2014, y 2015 en Columbia, Missouri, para investigar los efectos de herbicidas residuales comunes aplicados en maíz y soja sobre el establecimiento de trigo de invierno, rábano, centeno, Trifolium incarnatum, avena de invierno, guisante, Lolium perenne, y Vicia villosa . Los cultivos de cobertura fueron evaluados por reducciones en el establecimiento y la biomasa 28 d después de la emergencia(DAE). La precipitación desde la aplicación del herbicida hasta la siembra del cultivo de cobertura fue mucho mayor en 2014 y 2015, lo que resultó en menos efecto residual de los herbicidas en estos años al compararse con 2013. Cuando se promediaron todos los herbicidas evaluados en estos experimentos, el orden general de sensibilidad de los cultivos de cobertura a los residuos de herbicidas de mayor a menor fue guisantes = T. incarnatum > rábano > L. perenne > V. villosa > trigo > avena de invierno > centeno. El centeno tuvo el menor número de instancias en que se redujo la biomasa o el número de plantas establecidas con solamente cuatro de 27 herbicidas afectando negativamente el establecimiento. Pyroxasulfone redujo consistentemente la biomasa de L. perenne y avena de invierno al menos 67% en los experimentos de maíz y soja. En el experimento de soja, productos que contenían imazethapyr y fomesafen resultaron en reducciones severas en el establecimiento y la biomasa en ambos años mientras que productos conteniendo flumetsulam resultaron en los mayores síntomas de daño por residuos de los herbicidas en el experimento de maíz. Los resultados de estos experimentos sugieren que varios herbicidas comúnmente usados en maíz y soja tienen el potencial de reducir el establecimiento de cultivos de cobertura, pero la severidad del daño dependerá del clima, la especie de cultivo de cobertura, y la combinación específica de herbicidas.